Measurement of parents’ awareness levels and knowledge accumulation on digital game content with existing measurement tools - Birol, Sefa Şahan; Birol, Elif (Journal of Dependence, 2022)
The aim of this study is to determine the detection availability of parents’ digital game content awareness or their knowledge about digital games with current gaming disorder or game addiction measurement tools. In the study, the scales developed related to internet and game addiction were examined using the compilation method. In the literature review, Council of Higher Education Thesis Center have been utilized for searching of doctoral and master’s thesis and Google Scholar and Ulakbim databases have been utilized for searching articles. The Turkish adaptation studies are also included with the original scales. As a result of the research; Internet Gaming Disorder Scale, Game Addiction Scale For Adolescents, Adolescent’s Computer Addiction Scale, Digital Game Addiction Tendency Scale, Digital Game Parental Mediation Scale, Digital Game Addiction Scale For Children, Digital Game Addiction Scale For University Students, Children’s Computer Game Addiction Scale, Onlıne Game Addıctıon Scale, The Gaming Addiction Identification Test And Videogame Addiction Scale For Children have been reached in the literature. Looking at the literature, it is observed that almost all of the measurement tools related to gaming disorder or game addiction are focused on determining the emotional states of individuals playing the game and the awareness of the parents about the games or their knowledge about the games are ignored. For this reason, it is important to develop a measurement tool that can measure the awareness and knowledge of parents about the digital games played by their children in different subheadings.
Keywords: Digital game; parent; child; scale; measuring tool